Aloe Vera Extract-Mediated CuO NPs as Catalysts for the Synthesis of 4-Hydroxy-3-Methoxybenzaldehyde-Connected Piperidine Derivatives and Their Antibacterial Activity - Ponnusamy Packialakshmi; Perumal Gobinath; Anis Ahamed; Hissah Abdulrahman Alodaini; Ashraf Atef Hatamleh; Mohamed Taha Yassin; Akbar Idhayadhulla; Radhakrishnan Surendrakumar (Journal of Chemistry)
We have designed an easy, affordable, and eco-friendly technique for Schiff base preparation of vanillin-coupled piperidine analogues using CuO NPs as a catalyst. Using a green chemistry strategy using copper oxide nanoparticles (CuO NPs) as a catalyst, a unique one-pot synthesis of Schiff base vanillin-linked piperidine derivatives (2, 2a-2j) may be generated, with a potential yield in a short reaction time. The CuO NPs were synthesized with the aloe vera extract. The newly synthesized piperidin-4-ylidene analogues were investigated using FT-IR, NMR (1H, 13C), mass spectra, and elemental analysis. The morphology of piperidine derivatives was studied using XRD and TEM. The compound 2a-2j was evaluated for antibacterial activity against gram +ve and gram −ve bacteria. Compound 2d is exceptionally active against (5.0 μg/mL, E. coli), and 2c is very effective against (4.0 μg/mL, L. plantarum) when compared to reference drug and other Schiff base of vanillin-associated piperidine derivatives. Finally, we concluded the compounds 2c and 2d have strong antibacterial activity and can be used as antibacterial drugs in the future.